Novel cationic fullerenes as broad-spectrum light-activated antimicrobials - Huang, Liyi (2009)
Photodynamic inactivation (PDI) is a rapidly developing antimicrobial technology which combines a non-toxic photoactivatable dye or photosensitizer (PS) in combination with harmless visible light of the correct wavelength to excite the dye to its reactive triplet state that will then generate reactive oxygen species (ROS) that are highly toxic to cells. Buckminsterfullerenes are closed-cage molecules entirely composed of sp2 hybridized carbon atoms and although their main absorption is in the UV, they also absorb visible light and have a long-lived triplet state. When C60 fullerene is derivatized with cationic functional groups it forms molecules that are more water-soluble and can mediate PDT efficiently upon illumination, and moreover cationic fullerenes can selectively bind to microbial cells. In this report we describe the synthesis and characterization of several new cationic fullerenes. Their relative effectiveness as broad-spectrum antimicrobial photosensitizers against Gram-positive, Gram-negative bacteria, and a fungal yeast was determined by quantitative structure function relationships.